Energy-Efficient Policy Based on Cross-Layer Cooperation in Wireless Communication. (3rd September 2014) - Zhang, Juan; Jiang, Hong; Jiang, Hesong; Chen, Chunmei
Abstract : Cooperative communication has emerged as a new wireless network communication concept, in which parameter optimization such as cross-layer cooperation plays an important role. Heuristic evaluation postdecision state learning algorithm (HE-PDS) is proposed in cross-layer cooperation. The proposed algorithm exploits the determinate state information and jointly considers the transmitting power and channel state condition at the physical layer and the buffer congestion control at the media access control layer. The experimental results show that the cumulative average total costs of HE-PDS algorithm decrease about ten times and 8% under the maximum delay and throughput constraints and the power costs decrease about 50% and 28% under various delay limits and about 100% and 56% under the different throughput constraints than the traditional Q algorithm and PDS algorithm, demonstrating that the proposed algorithm has much better energy-efficient performance and faster convergence speed and outperforms the traditional Q learning algorithm and PDS learning algorithm.